ELECTRONIC MODULE (E-MODULE) AS INNOVATIVE LEARNING MEDIA TO INCREASE KNOWLEDGE AMONG NURSING STUDENTS - Ardyanti Syafitri; Yulia Kurniawati (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2022)
Electronic modules (e-modules) as innovative learning media that can be accessed anytime and anywhere are promised to increase nursing students' knowledge. However, there are still limited studies that examine the effectiveness of E-modules and the effect of E-modules on increasing student knowledge. This study aims to evaluate the effectiveness of the e-module on undergraduate nursing students' knowledge level. One group pre-posttest research design was conducted on 46 students recruited through purposive sampling. Respondents filled out the pretest, followed by studying the E-module material on spontaneous delivery compiled by maternity nursing experts for three reading periods in a week and working on a posttest questionnaire compiled by the researcher. Then the data were analyzed using the Wilcoxon test with a significance level of 0.05. Students' knowledge before giving the intervention was seen in the pretest results, with an average value of 72 and an increase in the average value in the posttest after the intervention was given to 97. So there was a significant effect of e-module as a learning medium on increasing student knowledge (p =0.00). The E Module has been proven to be effective in increasing knowledge. Still, nursing education and science continue to develop, so regular updating of the content of the e-module is needed and combining it with nursing moral values is essential because good moral attitudes are also the focus of nursing education.